2013
DOI: 10.3349/ymj.2013.54.6.1484
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Inferior Mesenteric Vein Ligation and Collateral Vessels to Splenic Flexure: Anatomical Landmarks, Technical Precautions and Clinical Significance

Abstract: PurposeOur aim to assess clinical significance of the relation between inferior mesenteric vein ligation and collateral blood supply (meandering mesenteric artery) to the splenic flexure with elaboration more in anatomical landmarks and technical tips.Materials and MethodsWe review the literature regarding the significance of the collateral vessels around inferior mesenteric vein (IMV) root and provide our prospective operative findings, anatomical landmarks and technical tips. We analyzed the incidence and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Adequate vascular supply of the left colon depends on the patency of the inferior mesenteric artery, the left colic artery but also relies on patency of the middle colic artery and the marginal Drumond and eventually Riolan arcades [ 29 , 30 ]. Anatomic variations are frequent, and aberrations such as absence of the middle colic artery or inadequate vascularization of the splenic flexure are frequent (up to 25 %) [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate vascular supply of the left colon depends on the patency of the inferior mesenteric artery, the left colic artery but also relies on patency of the middle colic artery and the marginal Drumond and eventually Riolan arcades [ 29 , 30 ]. Anatomic variations are frequent, and aberrations such as absence of the middle colic artery or inadequate vascularization of the splenic flexure are frequent (up to 25 %) [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of high ligation of the vessels to achieve optimal oncological results [ 29 ] suppresses the vascular supply from the left colic artery, and vascularization of the proximal colon is dependent on marginal vessels running off the middle colic artery. With the progressive increase in the aging population undergoing surgery for colorectal disease, radiation, vascular disease can also be a factor of insufficient vascular supply, even in the case of low ligation of the inferior mesenteric artery.…”
Section: Discussionmentioning
confidence: 99%
“…Careful attention should be paid to this area in what we call the"IMV critical zone". 28 In our recently published article, we studied this zone in detail and we found that in type A and B (Fig. 1a, b, c) the arc of Riolan "meandering" artery passes across the IMV or parallel to it respectively.…”
Section: Inferior Mesenteric Vein (Imv) Ligationmentioning
confidence: 95%
“…Thus ligation of IMV at these levels needs to be carefully attempted to avoid injury to the collateral vessels. 28 In certain circumstances the collateral vessels will be supplying the descending colon while the marginal artery is absent so incidental injury to collateral vessels might lead to ischaemia, necrosis, leak and stricture.…”
Section: Inferior Mesenteric Vein (Imv) Ligationmentioning
confidence: 99%
“…Vascular and abdominal surgeons are aware of this important collateral pathway between the IMA and the SMA. Indeed, inadvertent ligation or section of this important collateral network during aortic or abdominal surgery and especially in the presence of under-diagnosed stenosis of the SMA may have disastrous consequences, especially on the small intestine and left colon [ 29 30 ].…”
Section: Introductionmentioning
confidence: 99%